Locations & patterns of public space conflict in the UNESCO World Heritage Site, George Town, Penang, Malaysia / Muhamad Ferdhaus ... [et al.] - Ferdhaus, Muhamad; Zainol, Halmi; Abd Rahim, Asyirah; Muhammad, Zikri (Universiti Teknologi MARA, Perak, 2021)
One of the UNESCO World Heritage Sites in Malaysia is in George Town, Penang. Most of the space in this UNESCO World Heritage Site has various business activities. Traders work on a regular basis in the existing space or public space. Meanwhile, the hawkers move from one place to another. However, there are also traders and hawkers misusing and doing business in public space resulting in public space conflicts. The objectives of this study are to identify the location and patterns of public space conflict. The location of the conflict area has been marked and recorded for a more in-depth study. Data collection had been done and had found that the development of permanent building by the traders and hawkers had resulted in insufficient public space. Public space is essential in ensuring the sustainability of the environment.